Hypersecretion of OmlA antigen in Corynebacterium glutamicum through high-throughput based development process - Sun,M; Gao,AX; Ledesma-Amaro,R; Li,A; Wang,R; Nie,J; Zheng,P; Yang,Y; Bai,Z; Liu,X (Applied Microbiology and Biotechnology, 2022)
Outer membrane lipoprotein A (OmlA) is a vaccine antigen against porcine contagious pleuropneumonia (PCP), a disease severely affecting the swine industry. Here, we aimed to systematically potentiate the secretory production of OmlA in Corynebacterium glutamicum (C. glutamicum), a widely used microorganism in the food industry, by establishing a holistic development process based on our high-throughput culture platform. The expression patterns, expression element combinations, medium composition, and induction conditions were comprehensively screened or optimized in microwell plates (MWPs), followed by fermentation parameter optimization in a 4 × 1 L parallel fermentation system (CUBER4). An unprecedented yield of 1.01 g/L OmlA was ultimately achieved in a 5-L bioreactor following the scaling-up strategy of fixed oxygen mass transfer coefficient (kLa), and the produced OmlA antigen showed well-protective immunity against Actinobacillus pleuropneumoniae challenge. This result provides a rapid and reliable pipeline to achieve the hyper-production of OmlA, and possibly other recombinant vaccines, in C. glutamicum.Key Points• Established a holistic development process and applied it to potentiate the secretion of OmlA.• The secretion of OmlA reached an unprecedented yield of 1.01 g/L.• The recombinant OmlA antigen induced efficient protective immunity.